PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERKOTAAN DI DESA KETAON KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Harjanta, Jana (Transformasi, 2014)
The results showed that the process of making plans a program of activities has been through thestages recommended in the Guidelines for the Implementation of PNPM-MP at Ketaon Village.Starting RWT (Rapat Warga Tahunan) which accountability of BKM (Badan KeswadayaanMasyarakat) to communities and a program of activities and make plans for the next year. Allprogram activities are planned to be implemented, because the process is always accompaniedby a facilitator, by making of the program plan, formation of KSM (Kelompok SwadayaMasyarakat), proposal development activities, the implementation of activities to preparingreports KSM accountability. Communities of Gakin (Keluarga Miskin) feel very fortunate withthe program and they generally expect these programs continue.Keywords: Rural, Development, Public, Welfare